Perfectionism and sporting practice. Functional stress regulation in adolescence - González-Hernández, Juan; Muñoz-Villena, Antonio Jesús (Anales de Psicología / Annals of Psychology, 2018)
Systematic practice of physical activity (PA) in childhood and adolescence enables the development of functional resources for subjective perception of well-being, stimulation of cognitive processes, and construction of the personality. The development of perfectionist beliefs is currently seen as a functional characteristic linked to positive aspects (positive affect, self-esteem, etc.), while its dysfunctional aspects have been associated with anxiety and stress. The aim of this study is to identify which indicators of perfectionism provide functional conditions/skills that, in combination with the level of practice of physical activity, facilitate stress regulation. A sample of 365 adolescents (183 girls and 182 boys) aged between 13 and 17 participated. The results show that as the intensity of physical activity increases, there are significant changes in the indicators for functional perfectionism (high personal standards and organisation), with reference to facilitating (at moderate levels) or limiting (if excessive or absent) perceived stress and, above all, increased intensity of physical activity accentuates dysfunctional perfectionism patterns. This research has made it possible to identify active psychological processes that influence functional or dysfunctional psychological responses in adolescents depending on their level of perfectionism and the intensity of practise of PA.